INTERKULTURNA KNJIŽEVNA KROATISTIKA (Filološke pripombe, 2019)
By using the examples of the recent and contemporary Croatian literature, the article demonstrates the need of broader contextualisation of the Croatian literature in the context of Croatian studies as the foreign/second language, considering the different programmes of Slavic studies throughout the world. It also stresses the emergence of the intercultural literature, or rather of the possibility of the intercultural history of literature, from which questions are set about the relation with the neighbouring literatures in the context of a greater engagemen to experts for other Slavic languages and literatures.